The Effect of Environmental, Social, and Governance (ESG) Disclosure and Intellectual Capital on the Financial Performance of Energy Sector Companies Listed on the Indonesian Stock Exchange (IDX) for the 2022–2024 Period - Nadiyah Kharisma Ataya; Henryanto Wijaya (CV. Publikasi Indonesia, 2026)
This study aims to obtain empirical evidence on the effect of ESG disclosure and Intellectual Capital on the financial performance of energy sector companies listed on the IDX for 2022–2024. A quantitative causal design was applied to 22 companies selected through purposive sampling, yielding 66 firm-year observations. Financial performance was measured using Return on Assets (ROA), ESG disclosure using the Global Reporting Initiative (GRI) index, and Intellectual Capital using the Value-Added Intellectual Coefficient (VAIC), analyzed through panel data regression with the Fixed Effect Model. Results show ESG disclosure has a negative, insignificant effect on ROA, while Intellectual Capital has a positive and significant effect. The findings indicate ESG disclosure is still treated as a compliance cost, whereas efficient intellectual capital management is a key driver of profitability in the energy sector. The global business paradigm has shifted from a purely profit-oriented focus toward integrating sustainability and intangible value-creation factors into corporate performance assessment. ESG disclosure and Intellectual Capital (IC) have become increasingly relevant non-financial indicators, particularly for energy sector companies that face high environmental and social risk exposure, yet prior studies on their relationship with financial performance remain inconsistent, and evidence specific to the energy sector on the Indonesia Stock Exchange (IDX) in recent periods is still limited.